STRATEGI MANAJEMEN KOMUNIKASI DIGITAL DALAM MENINGKATKAN REPUTASI INSTITUSI PENDIDIKAN TINGGI DI ERA DISRUPSI MEDIA - Limbert Hutahaean; Gunardi Gunardi; Nana Sujana (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Digital transformation has fundamentally reshaped communication patterns in higher education institutions in building and maintaining their reputations. Media disruption—characterized by platform convergence, accelerated information flows, and increased public participation—requires universities to develop adaptive and data-driven digital communication management strategies. This study aims to analyze digital communication management strategies in enhancing the reputation of higher education institutions and to formulate a conceptual model relevant to the dynamics of the digital era.The research employs a qualitative approach with a multiple case study design involving three higher education institutions in Indonesia. Data were collected through in-depth interviews, social media observation, and analysis of communication policy documents. The data were analyzed using thematic analysis, including open, axial, and selective coding procedures. The findings reveal that effective digital communication strategies consist of four main stages: strategic planning based on institutional positioning, narrative content production through academic storytelling, management of two-way engagement, and reputation monitoring based on digital analytics. The results also indicate that the integration of communication management and social media data analysis significantly contributes to strengthening public trust and enhancing institutional image.This study proposes the “Adaptive Digital Communication Strategy Model” as a conceptual contribution to the development of communication management in higher education institutions.